Feeding behavior of premature infants according to the method of introducing new foods: a cross-sectional study through a family survey - Siri Schuchner, Alina; Matarazzo Zinoni, Milagros (Revista de Investigación en Logopedia, 2025)
Notable difficulty exists in reaching consensus in relation to recommendations for introducing complementary feeding in the premature infant due to the existence of acute and chronic conditions, the immaturity of the infant’s systems, eating problems from birth, risk of undernourishment, and poor growth rates. The Baby-Led Weaning (BLW) method shows benefits in several developmental areas. The aim of this study is to stablish if the introduction of complementary feeding through BLW improves the eating behaviour in preterm infants. We carry out an observational and retrospective study in which families of preterm infants answer the survey “Problematic Mealtime Behaviours” subscale of the PediEAT scale. This assessment tool sorts infants with feeding problems into groups displaying no concern, concern, or high concern. Other variables are also considered: gestational age, birth weight, enteral feeding, respiratory support, postmenstrual age at which independent oral feeding is achieved, the age at which complementary feeding is introduced, the type of infant nursing used (breast- or bottle-feeding). A total of 168 surveys are included. The mean corrected age is 14.60 months, and the mean gestational age is 33.41 weeks. Significant differences were found between the score obtained in the “Problematic Mealtime Behaviours” subscale and the variables complementary feeding method chosen and postmenstrual age at which independent oral feeding is achieved. The BLW method may be a better choice as a preventive step for feeding behaviour problems in preterm infants.